Bringing the web up to speed with WebAssembly. - Rossberg, Andreas; Titzer, Ben L.; Haas, Andreas; Schuff, Derek L.; Gohman, Dan; Wagner, Luke; Zakai, Alon; Bastien, J. F.; Holman, Michael (Communications of the ACM, 2018)
This article discusses the implementation of the low-level computer programming language for software known as WebAssembly. The authors comment on the use of WebAssembly in advanced web applications, including three-dimensional visualization, audio and video software, and gaming. The benefits of WebAssembly include its ability to function independent of the computer hardware and operating system on which it runs.